2021
DOI: 10.1002/jcp.30346
|View full text |Cite
|
Sign up to set email alerts
|

TRIM11 suppresses ferritinophagy and gemcitabine sensitivity through UBE2N/TAX1BP1 signaling in pancreatic ductal adenocarcinoma

Abstract: Gemcitabine is first‐line chemotherapy for pancreatic cancer, however, the development of resistance limits its effectiveness. The tripartite motif‐containing 11 (TRIM11) protein plays crucial roles in tumor development and undergoes auto‐polyubiquitination to promote interactions in selective autophagy. Therefore, Understanding whether TRIM11 is involved in ferritinophagy and gemcitabine resistance in pancreatic cancer is critical in developing pancreatic cancer therapeutics. TRIM11 expression was validated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Additionally, TRIM11 can activate MAPK or PI3K/AKT signaling pathways to promote tumor cell proliferation, invasion, and migration 22 . Shang et al identified that TRIM11 suppresses ferritinophagy in pancreatic ductal adenocarcinoma 23 . So, this study elucidates the role and potential mechanism of TRIM11 in ferroptosis of NSCLC.…”
Section: Introductionmentioning
confidence: 77%
“…Additionally, TRIM11 can activate MAPK or PI3K/AKT signaling pathways to promote tumor cell proliferation, invasion, and migration 22 . Shang et al identified that TRIM11 suppresses ferritinophagy in pancreatic ductal adenocarcinoma 23 . So, this study elucidates the role and potential mechanism of TRIM11 in ferroptosis of NSCLC.…”
Section: Introductionmentioning
confidence: 77%
“…In this study, we first identified that TRIM11 served as a novel Axin1-binding protein and expanded the role of TRIM11 in GC. Previously, TRIM11 upregulation had been detected in a series of human cancers, such as pancreatic ductal adenocarcinoma, renal clear cell carcinoma, ovarian cancer, and breast cancer [11,20,35]. Luo and Wang showed that TRIM11 upregulation was positively correlated with advanced pathological stage, large tumor size, and poor prognosis in GC [19].…”
Section: Discussionmentioning
confidence: 99%
“…Tripartite motif 11 (TRIM11), a RING-type E3 ubiquitin-protein ligase, is reported to be involved in several human malignant processes, including exacerbated proliferation, metastasis, angiogenesis, and chemoresistance [11][12][13]. Previous studies have shown that TRIM11 is upregulated and associated with tumor growth and metastasis in glioma, lung cancer, hepatocellular cancer, and breast cancer [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, UBE2N has a similar role to TRIM11 in regulating the autophagic pathway. It was demonstrated that UBE2N interacts with TRIM11, thereby promoting TRIM11-mediated ferritin phagocytosis and resistance to gemcitabine in PC ( 45 ).…”
Section: Class I E2s In Digestive System Cancersmentioning
confidence: 99%